Changes in gamma‐aminobutyric acid and glutamate/glutamine levels in the right thalamus of patients with episodic and chronic migraine: A proton magnetic resonance spectroscopy study. Issue 1 (18th January 2023) - Zhang, Xueyan; Wang, Wei; Bai, Xiaoyan; Zhang, Yingkui; Yuan, Ziyu; Tang, Hefei; Zhang, Xue; Li, Zhiye; Zhang, Peng; Hu, Zhangxuan; Zhang, Yaqing; Yu, Xueying; et al.
Abstract: Objective: To explore gamma‐aminobutyric acid (GABA) and glutamate/glutamine (Glx) levels in the right thalamus of patients with episodic migraine (EM) and chronic migraine (CM) and their effects on the chronification of migraine. Background: Migraine affects approximately 1 billion people worldwide, with 2.5%–3% of people with EM progressing to CM each year. Magnetic resonance spectroscopy studies have revealed altered GABA and Glx levels in the thalamus of patients with migraine without aura, but these neurometabolic concentrations are underexplored in the thalamus of patients with CM. Methods: In this cross‐sectional study, patients with EM and CM were recruited. Mescher‐Garwood point resolved spectroscopy sequence was used to acquire neurotransmitter concentrations in the right thalamus of patients with EM and CM and matched healthy controls (HCs). Results: A total of 26 patients (EM, n  = 11; CM, n  = 15) and 16 age‐ and sex‐matched HCs were included in the analysis. There were significantly lower GABA+/Water levels in the right thalamus of the CM group (mean ± standard deviation: 2.27 ± 0.4 [institutional units]) than that of the HC group (2.74 ± 0.4) ( p  = 0.026; mean difference [MD] = −0.5 [i.u.]), and lower Glx/Cr levels in the EM group (mean ± SD: 0.11 ± < 0.1) than in the HCs (0.13 ± < 0.1) and CM group (0.13 ± < 0.1) ( p  = 0.023, MD < −0.1, and p  = 0.034, MD < −0.1, respectively). The GABA+/Glx ratio was lower in the CM group (mean ± SD: 0.38 ± 0.1) compared to the EM group (0.47 ± 0.1) ( p  = 0.024; MD = −0.1). The area under the curve for GABA+/Water levels in differentiating patients with CM from HCs was 0.83 (95% confidence interval 0.68, 0.98; p  = 0.004). Correlation analyses within the migraine group revealed no significant correlation between metabolite concentration levels and headache characteristics after Bonferroni correction. Conclusion: Reduced GABA+/Water levels and imbalance of excitation/inhibition in the right thalamus may contribute to migraine chronification.